2020
DOI: 10.1002/jcla.23471
|View full text |Cite
|
Sign up to set email alerts
|

The role ofBacillus acidophilusin osteoporosis and its roles in proliferation and differentiation

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…We can use these results to develop clinical applications and regulate the inflammation with controlled changes in intestinal butyrate concentration. Although the reported butyrate concentrations in the literature are in both the micromolar range , and the millimolar range, ,, we selected the micromolar range of butyrate, since experimental data for biodistribution of butyrate in that range is available. , Our current model is scalable to study the effect of the millimolar range of butyrate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We can use these results to develop clinical applications and regulate the inflammation with controlled changes in intestinal butyrate concentration. Although the reported butyrate concentrations in the literature are in both the micromolar range , and the millimolar range, ,, we selected the micromolar range of butyrate, since experimental data for biodistribution of butyrate in that range is available. , Our current model is scalable to study the effect of the millimolar range of butyrate.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Lucas et al reported 19.55% reduction in osteoclasts and no significant change in osteoblasts. Another experimental observation showed increased proliferation, differentiation, and maturation of osteoblasts and inhibition of osteoclasts’ proliferation due to LGG and butyrate . Some of these variations are certainly explainable by differences in experimental protocols and treatments and characteristics of animal models (e.g., age, sex, strain, and vendor) between studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, for the treatment of postmenopausal osteoporosis, intestinal flora, especially intestinal probiotics, has been proven to be a potential therapeutic strategy [ 49 ]. Among them, Lactobacillus rhamnosus can stimulate bone formation by increasing estrogen [ 50 ]. The study found that prebiotics can increase the number of probiotics such as lactobacilli and butyric acid bacteria to promote the secretion of more short-chain fatty acids, thereby reducing the intestinal PH value and increasing the solubility of calcium in the intestinal lumen, thus increasing the bone mineral content and bone mineral density of young people [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…ALP aktivitesinin arttığı OK konsantrasyonunun yükseldiği ve RUNX2, RANK, NFATc1, cathepsin K, DC-STAMP, OSCAR, WNT2 ve CTNNB1 yükseldiği osteoblastlarda gösterilmiştir. Osteoklastlar içinde tersi gerçekleşmiştir (20). İnsan kemik iliği MKH osteoblastik farklanmasında PLLA scaffoldu ile verilen probiyotik nisin tedavisinin osteoblastik farklanmada etkili olduğu gösterilmiştir.…”
unclassified